Maximal Operator on Carleson Curves in Local Generalized weighted Morrey Spaces - Celik, Süleyman (Association of Mathematicians (MATDER), 2026)
In this paper, we provide boundedness of strong and weak types for the maximum operator M in the generalized weighted Morrey space Mp,? (?, w) defined on Carleson curves ? and the local generalized weighted Morrey space LM{t0} p,? (?, w). © MatDer.
Keywords: boundedness; Carleson curve; local generalized weighted Morrey space; maximal operator